Learning with a digital escape room game: before or after instruction? - Josef Buchner; Martina Rüter; Michael Kerres (The Asia-Pacific Society for Computers in Education (APSCE), 2022)
Abstract In this study, we investigated whether playing an escape room game after explicit instruction (instruction-first group, N = 20) is more effective to learn about copyright and media law than playing the game before explicit instruction (problem-solving-first group, N = 21). This is an important question as escape room games are complex, problem-based learning environments that can overwhelm learners and thus hinder the acquisition of knowledge and skills. According to cognitive load theory, preparing learners with explicit instruction before problem-solving activities can overcome this problem leading to better learning. However, in the productive failure paradigm problem-solving before explicit instruction is seen as more effective, especially when it comes to the application of newly acquired knowledge to solve novel problems. Based on these two theories, we conducted an experiment and found that playing the developed digital escape room game after explicit instruction was more effective for knowledge retention and domain-specific self-efficacy with at the same time lower cognitive load. However, we found no differences regarding the application of knowledge as both groups scored equally high on transfer tasks. The result is discussed considering previous productive failure studies mostly conducted in the science and engineering domain. In sum, the instruction first approach proved to be effective for both knowledge acquisition and knowledge application, leading to higher domain-specific self-efficacy and lower cognitive load. Therefore, we conclude that the implementation of escape room games after instruction is an effective instructional approach and better suited to promote learning than playing escape room games before instruction.